Validity and Social Experimentation : Donald Campbell's Legacy. - Bickman, Leonard (Social Research Methods., 2000)
Leading social research methodologists and evaluators address the issues of validity, research design and social experimentation in this first of two volumes inspired by the work of Donald Campbell and sponsored by the American Evaluation Association. Each chapter is designed to offer readers insight into such issues as validity applied to meta-analysis, subject selection problems in randomized experiments, time-series designs and quasi-experiments, and the logic of ruling out rival hypotheses. Anyone engaged in social research will find this book a thought-provoking and inspiring read for their work.